Patient outcomes and thoracic aortic volume and morphologic changes following thoracic endovascular aortic repair in patients with complicated chronic type B aortic dissection - Andacheh, Iden David; Donayre, Carlos; Othman, Ahmad Faidzal; Walot, Irwin; Kopchok, George; White, Rodney A.M.D. (ELSEVIER, 2012)
True and false lumen changes and patient outcomes following thoracic endovascular aortic repair (TEVAR) for patients with stable type B dissection have been described by the The Investigation of Stent Grafts in Aortic Dissection (INSTEAD) trial. However, these changes have not been described in TEVAR patients treated for complications of chronic dissection. Methods A single-institution study was conducted of 73 prospectively evaluated patients treated for complications of chronic type B dissection from 2002 to 2010. Spiral computed tomography reconstructions using M2S (Medical Media Systems, West Lebanon, NH) were analyzed for sequential changes in aortic volume and diameter during patient follow-up. Changes in aortic volume and diameter were tabulated as a percent change from preoperative values. Patient outcomes were determined by sequential evaluations postprocedure. Results TEVAR was successfully performed in 72 out of the 73 patients (99%). Indications for intervention were aortic enlargement (n = 62), failure of medical management (n = 7), and perforation (n = 4). The 30-day all-cause mortality rate was 14%; events were due to retrograde dissection (n = 4), cardiac-related (n = 4), and rupture (n = 2). Eleven out of the 72 patients (15%) required a secondary procedure for endoleak (n = 7) and persistent distal perfusion of the false lumen (n = 4). Mean percentage expansion of the thoracic true lumen was noted during the follow-up period: 38%, 46%, 71%, and 114% at 1-, 3-, 6-, and 12-month follow-up, respectively. Concomitant regression of the thoracic false lumen of −65%, −68%, −84%, and −84% was observed at the same intervals, respectively. Patients with an initial extension of the thoracic dissection into the infrarenal aorta (n = 46) had an increase in mean percentage change of aortic diameter and volume to 21% and 17% at 1 year, respectively. By contrast, in the patient group without infrarenal dissection (n = 14), the infrarenal aortic diameter and volume remained relatively unchanged at 3% and −0.9%, respectively, at 1-year postintervention. Conclusions TEVAR is a potential treatment option for patients experiencing complications of chronic type B dissection. During follow-up, there is a predictable expansion of the thoracic true lumen and regression of the thoracic false lumen. These findings correlate with those of the INSTEAD trial, which demonstrated false lumen regression and true lumen expansion in a cohort of patients with stable type B dissection. However, many patients with extension of thoracic dissection into the infrarenal aorta demonstrate continued aortic dilation and, on occasion, the need for secondary intervention for persistent distal perfusion. Further analysis is needed in this subgroup of patients so as to better determine potential predictors and the clinical significance of post-TEVAR infrarenal expansion. Moreover, further investigations may support a role for secondary endovascular intervention in remedying persistent infrarenal aortic expansion after TEVAR for chronic dissection.